2017
DOI: 10.1039/c6cc09324h
|View full text |Cite
|
Sign up to set email alerts
|

Superfluorinated and NIR-luminescent gold nanoclusters

Abstract: A novel class of superfluorinated and NIR-luminescent gold nanoclusters were obtained starting from a branched thiol, bearing 27 equivalent F atoms per molecule. These unprecedented clusters combine in a unique nanosystem both NIR photoluminescence andF NMR properties, thus representing a promising multimodal platform for bioimaging applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 29 publications
1
34
0
Order By: Relevance
“…The aggregation-induced luminescence of NCs has been achieved either using solvent-induced aggregation or addition of additives such as ionic polymers, proteins or peptides [74][75][76]. Recently, Dichiarante et al reported NIR-luminescent AuNCs bearing superfluorinated (SF) ligands with strong emission at 1050 nm with a quantum yield of 12% [77]. An extensive account of the PL of NCs is beyond the scope of this review and has been previously summarized in several reports [54,[78][79][80][81][82].…”
Section: Review Luminescent Gold Nanoclustersmentioning
confidence: 99%
“…The aggregation-induced luminescence of NCs has been achieved either using solvent-induced aggregation or addition of additives such as ionic polymers, proteins or peptides [74][75][76]. Recently, Dichiarante et al reported NIR-luminescent AuNCs bearing superfluorinated (SF) ligands with strong emission at 1050 nm with a quantum yield of 12% [77]. An extensive account of the PL of NCs is beyond the scope of this review and has been previously summarized in several reports [54,[78][79][80][81][82].…”
Section: Review Luminescent Gold Nanoclustersmentioning
confidence: 99%
“…This can be achieved by PEGylation, [76] encapsulation with hydrophilic polymer [77] or micellization [78] . Labelling of the particles with small amount of fluorescent ligands [76] may be necessary: several types of nanoparticles possess inherent fluorescent properties which simplifies the design of dual 19 F/OFI probes [77,79] . This is especially true for smaller Au‐cores (1–2 nm diameter or less) which emit in the NIR region [79] and provide excellent alternatives to organic NIR emitters.…”
Section: Dual 19f Mri/ofi Probesmentioning
confidence: 99%
“…Nevertheless, the polydispersity of the Au‐core resulted in a small splitting of the main sharp 19 F NMR resonance at −71.14 ppm. Another significant issue with the probe was its poor solubility in aqueous environment, which may be a limiting factor in potential diagnostic applications [79] …”
Section: Dual 19f Mri/ofi Probesmentioning
confidence: 99%
“…Atomic nanoclusters with large Stokes shifted emission, size tunable luminescence, good biocompatibility, high photostability and regular structure, are ideal candidates for biological imaging and chemical sensing . Among the multitude of nanoclusters, the case of thiol‐protected nanoclusters is especially intriguing owing to their stability due to the attainment of “magic number” .…”
Section: Introductionmentioning
confidence: 99%